Efektivitas Penggunaan Aplikasi Google Forms dalam Pelaksanaan Penilaian Tengah Semester Berbasis Online di Madrasah Aliyah Negri 1 Tegal - Agus Saputra; Ainun Nasikha; Ikhda Fitriyani; Mohamad Daffa Amanulloh; Raisah Muthmainnah; Resi Agustien; Tholchah Kais (La-Tahzan: Jurnal Pendidikan Islam, 2024)
This research was motivated by the technological advances used since Covid-19 that were still used to evaluate student learning outcomes in the Midterm Assessment at Madrasah Aliyah Negeri (MAN) 1 Tegal. This study aims to analyze the effectiveness of using the Google Forms application in the implementation of online-based Midterm Assessment (PTS) at MAN 1 Tegal. The approach used in this research is a quantitative approach descriptive and qualitative methods. Determination of the sample in this study using purposive sampling technique, namely students of XII MIPA 4 and XII MIPA 6 classes, two teachers involved in the implementation of PTS, and the Head of Madrasah Curriculum. The data collection tools used include: questionnaires, observations, interviews, and documentation. While data analysis was carried out using quantitative descriptive analysis techniques by converting qualitative assessments into quantitative assessments with the percentage formula. The results showed that the use of Google Forms as an online PTS platform provided convenience in organizing exams, increasing time efficiency, and minimizing technical errors in question distribution. In addition, most students consider Google Forms easy to access and use, although there are some obstacles related to internet connection and validity of exam results. Overall, the Google Forms application is considered effective in supporting the implementation of the online-based PTS.